A decision support web service for allocating assets in counter-piracy operations given periodic environmental forecast updates. (15th May 2019) - Bourque, François-Alex; Grasso, Raffaele; Vicen-Bueno, Raúl; Cimino, Giampaolo; Braca, Paolo; Osler, John
The rise of piracy in the Gulf of Aden and off the coast of Somalia prompted several nations to direct their navies to conduct counter-piracy operations in that region of the world. A major challenge with such operations is the sheer size of the area to patrol. One way to address this problem is by noting that pirates are more likely to operate under favourable environmental conditions and to focus patrols in areas where such conditions prevail by generating maps of piracy risk based on environmental forecast. This contribution presents a system that invokes a multi-objective optimiser with each new forecast to help the decision makers plan operations over the course of days, weeks or months. Implemented using web-based technologies to mitigate for potential resource limitations at the client site, the resulting decision support system is demonstrated for a counter-piracy operation conducted off the coast of Somalia.